The Effects of Enzyme Supplementation on Performance, Carcass Characteristics and Some Blood Parameters of Broilers Fed on Corn-Soybean Meal-Wheat Diets - Hajati, H.; Rezaei, M.; Sayyahzadeh, H. (International Journal of Poultry Science, 2009)
In a completely randomized design the effects of a multi-enzyme (Endo-feed-W) supplementation on performance, carcass characteristics and some blood parameters of Cobb 500 broilers fed on corn-soybean meal-wheat diets were studied. The enzyme levels added to the diets were 0.00% (control) and 500mg kg-1 DM. Enzyme supplementation significantly improved body weight gain, feed to gain ratio, relative growth, energy and protein efficiency from 11-28 d of age. Adding enzyme significantly increased body weight gain, decreased feed intake and improved feed to gain ratio, energy and protein efficiency from 29-44 d of age (p<0.05). Body weight gain, feed intake, relative growth, energy and protein efficiency was increased and feed to gain ratio was decreased by enzyme supplementation from 29-44 d (p<0.05). Enzyme addition significantly increased carcass and thigh percentages at 44 d of age. Adding enzyme significantly increased the concentration of blood triiodothyronine (T3) at 28 and 42 d and reduced the concentration of blood thyroxin (T4) at 42 d of age. Enzyme inclusion increased the concentration of blood total cholesterol at 10, 28 and 42 d of age, however HDL-cholesterol and triglyceride concentrations increased at d 10 and 42 (p<0.05). The concentration of blood uric acid was significantly decreased at d 28 and 42 in broilers fed enzyme supplemented diets.